Development of projectile launcher for learning purpose - Aida Azwa, A. Halim (2007)
Idea to design and fabricate a projectile motion is come from a supervisor that gives a task and a title for this project. To design and fabricate this projectile motion it must compare with the other product that available in laboratory. To make sure the idea to design and fabricate the projectile launcher that can be used for projectile experiment the information about current design for projectile motion must search or get from the internet. Form there the information and idea to design and fabricate a projectile motion can be created. It includes many things about projectile motion design that wanted to gather accurate flight time data for projectiles. From there the efficiency of projectile motion analysis equation being determine. Whole of the project involve various methods like the concept design, the designing and also the fabrication process. After the assemble process complete the projectile launcher is tested to gather the flight time data for projectiles. Then the projectile motion analysis equation is solve from the time data. From the results the projectile launcher for projectile experiment was achieves the objective successfully. Overall in this project can bring a motivation and experience to conduct the various type of machine, train to work under the pressure, and also soft skill ability like time management, planning the task, negotiation skill and sell out the idea especially during work progress presentation.